The effectiveness of cognitive behavioral therapy for adolescent with body dissatisfaction, anxiety and self-esteem issues - Nordiana Terence; Norzihan Ayub; Patricia Joseph Kimong (Global Academic Excellence, 2023)
Body image dissatisfaction or negative body image is closely related to psychological and cultural factors. The issue of body dissatisfaction becomes very important to university and college teenagers as well as adults, as this problem arises when they are too obsessed with weight satisfaction, weight anxiety and physical attraction. This issue can have a drastic impact on adolescent’s anxiety and self-esteem, due to the fact that when their weight does not reach the desired level, they will experience disorders such as depression, lack of self -esteem and eating problems. In Malaysia, the issue of image dissatisfaction, anxiety and self-esteem is increasing every year. This is because nowadays teenagers are too obsessed and fixated with body image that it affects their health. In addition, some communities also consider that body size and weight should be ideal according to the wishes of the cultural culture so many children and adolescents choose to stay slim in order to be accepted by their peers. These problems of dissatisfaction, anxiety and self-esteem are formed from cognitive, perceptual and behavioral aspects. The cognitive aspect explains how an individual thinks about himself; the perceptual aspect is seen through how other individuals assess their bodies and the behavioral aspect is also how individuals treat their bodies as desired. Thus, using the cognitive behavioral therapy intervention module can help individuals to change their assumptions and beliefs about the problem of body image dissatisfaction.